Climate change hazards and the resilience of coastal cities in the Gulf Cooperation Council countries: A systematic review - Abdulla Almheiri; Jorge F. Montenegro; Ewane Basil Ewane; Midhun Mohan (City and Environment Interactions)
Climate change hazards continue to pose detrimental impacts on coastal cities in the Gulf Cooperation Council (GCC) countries (Saudi Arabia, UAE, Qatar, Bahrain, Kuwait, and Oman) of the Middle East, which undermines their climate resilience. The situation is exacerbated by the rapid urban development in coastal cities in the GCC countries over the past 20 years. This review study examined the climate change hazards that are having negative impacts on the resilience of coastal cities in the GCC countries using a systematic literature review approach. It also explores the urban resilience strategies implemented towards climate change hazards mitigation and adaptation in order to build climate-resilient coastal cities in the GCC countries. A total of 48 peer-reviewed articles were included in the systematic review derived from Scopus, WoS, and Google Scholar, covering the nine coastal cities in the six GCC countries. Most of the studies were focused on the coastal cities of Jeddah (30 %) in Saudi Arabia and Doha (24 %) in Qatar, compared to the other seven coastal cities in the GCC countries. Flooding, rising temperature, sea level rise, dust storms, cyclones, and migration of sand dunes were the six most reported climate change hazards, respectively, posing significant negative impacts on coastal cities and undermining their resilience to current and future climate change impacts. The various urban resilience strategies implemented against climate change hazards were categorised under five resilience dimensions: infrastructure resilience, social resilience, environmental resilience, economic resilience, and governance and policy resilience dimensions. The infrastructure resilience dimension was reported in 50.7 % of the studies, since it is the most implemented, while far less research attention was given to the environmental (14.5 %), government and policy (8.7 %), and economic (2.9 %) resilience dimensions of coastal cities in the GCC countries. The urban resilience strategies for climate mitigation and adaptation were reported to have successfully reduced the vulnerability of coastal cities to climate change hazards over the past decade, by improving their climate resilience. The findings contribute to informing urban planning policy-making focused on coastal environmental management in the coastal cities of the GCC countries that should further enhance the climate resilience of these coastal cities.